PathSync: Multi-User Gestural Interaction with Touchless Rhythmic Path Mimicry - Carter, M.; Velloso, E.; Downs, J.; Sellen, Abigail; O'Hara, Kenton; Vetere, F. (Proceedings of CHI 2016, 2016)
This paper reports on the first of a series of analyses aimed at comparing same room and video-mediated conversations for multiparty meetings. This study compared patterns of spontaneous speech for same room versus two videomediated conversations. One video system used a single camera, monitor and speaker, and a picture-in-a-picture device to display multiple people on one screen. The other system used multiple cameras, monitors, and speakers in order to support directional gaze cues and selective listening. Differences were found between same room and video-mediated conversations in terms of floor control and amount of simultaneous speech. While no differences were found between the video systems in terms of objective speech measures, other important differences are suggested and discussed.